2023
DOI: 10.3390/foods12071481
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Multilayer pH-Responsive Hydrogel Loaded Ganoderma lucidum Peptides

Abstract: To develop a safe, targeted, and efficient assembly of a stable polypeptide delivery system, in this work, chitosan, sodium alginate, and sodium tripolyphosphate were used as materials for the preparation of hydrogels. M-SCT hydrogels were prepared by ionic gelation and the layer-by-layer (LBL) method. The composite hydrogels exhibited excellent pH sensitivity and Ganoderma lucidum peptides (GLP) loading capacity. The prepared hydrogels were characterized and evaluated. The internal three-dimensional network s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, upon arrival at the location of colonic inflammation, the alkaline surroundings prompted an escalation in the swelling characteristics of chitosan, resulting in the expansion of the hydrogel and subsequent liberation of the Pt NPs. The methodology accomplished targeted treatment of colonic inflammation via Pt NPs [46]. A 2.5% DSS solution was employed over 8 days to simulate acute UC in mice (Figure 6A, ii).…”
Section: Protective Effect Of Pt Nps Against Colitismentioning
confidence: 99%
“…Nevertheless, upon arrival at the location of colonic inflammation, the alkaline surroundings prompted an escalation in the swelling characteristics of chitosan, resulting in the expansion of the hydrogel and subsequent liberation of the Pt NPs. The methodology accomplished targeted treatment of colonic inflammation via Pt NPs [46]. A 2.5% DSS solution was employed over 8 days to simulate acute UC in mice (Figure 6A, ii).…”
Section: Protective Effect Of Pt Nps Against Colitismentioning
confidence: 99%
“…After encapsulation, the digestion and thermal stability of GLP was improved, while the antioxidant activity of GLP was retained. This study suggested that the composite hydrogels had a great deal of potential as a peptide carrier for oral delivery [ 5 ].…”
mentioning
confidence: 99%